Gift-giving, sharing and commodity exchange at Bookcrossing.com: new insights from a qualitative analysis. Issue 4 (13th May 2014) - Simone Guercini, Professor; Corciolani, Matteo; Dalli, Daniele
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Through an empirical analysis of a consumption community, the purpose of this paper is to demonstrate that the theories of gift-giving, sharing and commodity exchange should not be kept separated but integrated into a unifying model. Design/methodology/approach – The paper provides new evidence about Bookcrossing.com, whose members share and give books as gifts; that is, physical goods rather than digital ones as in most of the communities considered in the literature. This community is analysed with qualitative tools, such as netnography, personal interviews and participant observation. Findings – The main result of the analysis of Bookcrossing is that gift-giving is not the only process responsible for value creation and distribution in consumption communities: sharing and commodity exchange also play a role. Furthermore, the paper provides new evidence about aspects of gift-giving and sharing that have received limited attention in the literature: collective reciprocity and anonymous sharing. Research limitations/implications – The limitations are related to the intrinsic properties of the methods employed (netnography, personal interviews and participant observation) and to the paper, which analyses only one community and one product category. The implications refer to the role of gift-giving in consumption communities and its relationships with other processes: consumer gift systems are not only gifting platforms, but they and the elements of sharing and commodity exchange need to be integrated. Practical implications – The empirical evidence and implications matter for the organisation and management of collaborative consumption platforms and the way in which traditional business models could and should interact with these platforms in an increasing number of businesses. Originality/value – The paper adds new evidence of and original insights into gift-giving and collective forms of exchange. Moreover, it provides managerial implications of the analysed community for the book publishing industry.